The (well)-(ill) being of the translator between languages-cultures - Coracini, Maria José (Revista Conexão Letras, 2017)
This article aims to discuss translation as a multicultural task: the translator is between languages-cultures, which constitute every language, In light of the (im)possible task of translating, the translator sees her/himself constantly in the contingency of making choices of all types, consciously or inconsciously: choice of vocabulary, syntax, morphology, semantics and so on. In the sphere of language, making choices necessarily assumes a gesture of interpretation. Then, to translate is to interpret and to interpret is a gesture of violence, according to Foucault. Therefore, translation is violence and inclusion, it is more than one word in a word, more than one language in a single language; translation is différance, in Derrida’s thought.